2005
DOI: 10.1111/j.1365-2273.2004.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative humidity of the external auditory canal in normal and abnormal ears, and its pathogenic effect

Abstract: The raised relative humidity in the external canal may explain the predisposition of certain abnormal ears to chronic discharge and infection. If the humidity of the canal could be brought down to a normal level, this could offer a new therapeutic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
1
12
1
1
Order By: Relevance
“…Hajjartabar reported that 32.21% of patients with otitis externa were women ( 18 ). Although women tend to be more health-conscious, most of the women in our study were housekeepers, which may have contributed to the condition as relative humidity can affect ear conditions, as reported previously in other studies on otitis in general ( 9 , 11 , 19 ).…”
Section: Discussionsupporting
confidence: 60%
“…Hajjartabar reported that 32.21% of patients with otitis externa were women ( 18 ). Although women tend to be more health-conscious, most of the women in our study were housekeepers, which may have contributed to the condition as relative humidity can affect ear conditions, as reported previously in other studies on otitis in general ( 9 , 11 , 19 ).…”
Section: Discussionsupporting
confidence: 60%
“…The use of an ointment instead of drops in the treatment of otitis externa can be seen from two points of view. On the one hand, the occlusive effect of an ointment may raise the humidity in the affected ear [15]. On the other hand, fewer hypersensitivity reactions are to be expected because no preservatives, which may cause allergic reactions, are required for water-free ointments, whereas eardrops are often preserved.…”
Section: Discussionmentioning
confidence: 97%
“…On the one hand, the occlusive effect of an ointment may raise the humidity [24] in the affected ear. On the other hand, fewer hypersensitivity reactions are to be expected because no preservatives, which may cause allergic reactions, are required for water-free ointments, whereas eardrops are often preserved.…”
Section: Discussionmentioning
confidence: 99%